An Analysis of Mobility Patterns in Sexual Homicide. Issue 2 (May 2020) - Chopin, Julien; Caneppele, Stefano; Beauregard, Eric
This article—based on a national data set ( N = 173)—focuses on extrafamilial sexual homicides and their spatial mobility. The study combines the location of the crime scene and the offenders and victims' residences in mobility crime triangles. The findings reveal that most of the homicides fall within the categories of offender mobility and total mobility. Our results show the validity of the distance decay function, with over 70% of homicides occurring within 10 km of the offender's residence. It appears that under certain circumstances, sexual murderers perceive their surroundings as a safe place to commit a homicide. Finally, the study proposes a four-category spatial typology of sexual homicide.